Development of a Learning Enrichment Material in Morphology: A Focus on Morphemes and Inflections - Ramos, Angelou O. (Asian Journal of Multidisciplinary Studies, 2019)
Morphological awareness comprises primarily knowledge about the pairing of sound and meaning in a language and the word formation rules that guide the possible combination of morphemes. If knowledge of word form and meaning are important to vocabulary acquisition, then it seems logical that those who are more gifted with regard to morphological awareness are better equipped to grow their vocabulary. This study aimed to develop a learning enrichment material in morphology to college students. Specifically, it sought to focus on morphemes and inflections as the 93 Education English major students were already grammatically competent on the use of derivational and inflectional morphemes with reference to the findings of the studies entitled “On Derivational Morphemes: Grammatical Competence of College Students” and On Inflectional Morphemes: Grammatical Competence of College Students” respectively. The descriptive survey method was utilized as the research described and attempted to interpret the overall level of grammatical competence on derivational and inflectional morphemes of Education English major students. Survey and written test questionnaires were used as instruments of this study on which findings revealed that majority of the college students were found to have high grammatical competence on derivational and inflectional morphemes. For this reason, development of a learning enrichment material focused on morphemes and inflections was deemed imperative.